Privacy protection key distribution protocol for edge computing - Jian SHEN; Tianqi ZHOU; Chen WANG; Huijie YANG (网络与信息安全学报)
Aiming at the privacy protection problem in the multi-application scenarios of edge computing, two policy-based key distribution protocols were proposed.The proposed protocols are based on the concept of constrained pseudo-random functions to achieve efficient and flexible policy selection.Specifically, based on the GGM pseudo-random number generator, the key distribution protocol with a prefix-predicate is constructed, which can effectively support lightweight and efficient key distribution.Moreover, based on the multilinear pairing, the key distribution protocol with a bit fixing predicate is constructed.This protocol can support flexible and fine-grained strategy selection and is suitable for dynamic and flexible multi-device scenarios in heterogeneous networks.Finally, the security proof of the proposed protocols is presented.